2007
DOI: 10.1080/13547500600943528
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal proteomic approach for protein profiling in blue mussels (Mytilus edulis) exposed to crude oil

Abstract: Peroxisomal proteomic protein profiles of exposure to marine pollution have been recently introduced in biomonitoring experiments. However, laboratory experiments to study the independent effect of common pollutants are needed to define a minimal protein expression signature (PES) of exposure to a specific pollutant. The aim of this study was to obtain PESs in blue mussels (Mytilus edulis) exposed to two different crude oil mixtures for future application in biomonitoring areas affected by oil spills. In the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…The hierarchical cluster analysis of the unique PES spots from the 2D maps that showed significant change in the abundance was able to distinguish the control group from exposed mussels. The data indicate that the PES obtained with DIGE are consistent with previous findings, and that the signatures can be used to biomonitor areas affected by oil spills and to assess oil exposure in the marine environment (Mi, Apraiz, & Cristobal, 2007). …”
Section: A Strategies For Protein Identificationsupporting
confidence: 89%
See 2 more Smart Citations
“…The hierarchical cluster analysis of the unique PES spots from the 2D maps that showed significant change in the abundance was able to distinguish the control group from exposed mussels. The data indicate that the PES obtained with DIGE are consistent with previous findings, and that the signatures can be used to biomonitor areas affected by oil spills and to assess oil exposure in the marine environment (Mi, Apraiz, & Cristobal, 2007). …”
Section: A Strategies For Protein Identificationsupporting
confidence: 89%
“…A number of proteins identified in this study had already been reported previously, thus validating the DIGE technique in environmental research. A recent publication was using DIGE technology to define minimal PES characteristic for blue mussels (Mytilus edulis) exposed to crude oil mixtures (Mi, Apraiz, & Cristobal, 2007). The hierarchical cluster analysis of the unique PES spots from the 2D maps that showed significant change in the abundance was able to distinguish the control group from exposed mussels.…”
Section: A Strategies For Protein Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported that environmental stress such as variation in salinity and temperature [96] or exposure to environmental contaminants such as heavy metals, xenoestrogen, and chlorinated compounds [94,97,98] has an impact on protein expression in different tissues of relevant aquatic organisms. Although gel-free methods using surface-enhanced laser desorption/ionization (SELDI) mass spectrometry have been investigated [99][100][101], environmental biomarker discovery still relies mainly on 2D gel electrophoresis and, to our knowledge, is lacking for aquaculture production [102][103][104]. However, there is no doubt that using a proteomic approach in combination with other biomarkers at physiological, behavioral, and biochemical levels will give a more precise set of biomarkers for assessing the exposure of penaeid shrimp to drugs and chemicals.…”
Section: Further Developmentsmentioning
confidence: 99%
“…They reported changes in the proteome of juvenile Atlantic cod (Gadus morhua) [83] of mussel Mytilus edulis exposed to PAH and alkyl phenols [84], to PCB and PAH ( [85]), in the clam Chamaelea galina exposed to PCB [86], to As [87] or the clam Ruditapes decussatus exposed to Cd [88].…”
Section: Toxins and Other Environmental Contaminants Detectionmentioning
confidence: 99%